2010
DOI: 10.3846/jbem.2010.15
|View full text |Cite
|
Sign up to set email alerts
|

Internationalization Paths of Chinese Firms: Evidences From an Emerging Economy

Abstract: In this paper, an empirical study is conducted to explore the paths of internationalization for Chinese manufacturing firms. Correspondence analysis was employed to examine the relationship between the internationalization paths and the firms' form of ownership. It reveals that the internationalization paths of Chinese firms appear to be in a form of terrace structure, more firms adopting the rudimentary levels than the more matured courses of internalization. The findings indicate that Chinese firms are chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In recent years, China has received substantial external capital inflows after having suffered capital or wealth flight for the previous 10 years [10]. A previous study has suggested that Chinese OFDI supports international finance [11]. Researchers in the international business and emerging market economies literature have predominantly used Chinese FDI data (cross-sectional and survey data) to map where Chinese investment is located and what drives Chinese investment in a particular region.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, China has received substantial external capital inflows after having suffered capital or wealth flight for the previous 10 years [10]. A previous study has suggested that Chinese OFDI supports international finance [11]. Researchers in the international business and emerging market economies literature have predominantly used Chinese FDI data (cross-sectional and survey data) to map where Chinese investment is located and what drives Chinese investment in a particular region.…”
Section: Introductionmentioning
confidence: 99%
“…Internationalization strategies of developed banks have attracted a fair degree of research interest, but internationalization strategies of emerging banks remain largely underinvestigated (Aulakh, Kotabe, & Teegen, 2000;Zeng, Shen, Tam, & Wan, 2010). While banks from developed countries may face constraints to sustainable internationalization due to low levels of capital despite a positive market image, banks from emerging economies may, alternatively, suffer from a relatively negative image in international markets despite high levels of capital (Petrou, 2009).…”
Section: Chinese and Brazilian Banks In Switzerlandmentioning
confidence: 99%
“…the institutional environment and industrial competition) may play important roles in explaining the internationalization behavior of firms (Casillas and Moreno-Menéndez, 2013;Chetty et al, 2014). A significant corpus of studies has shown that SOEs differ from traditional multinationals in that state ownership, political connections, and state control are the crucial factors encouraging SOEs to internationalize and compete against their counterparts in global markets (Cuervo-Cazurra et al, 2014;Hoskisson et al, 2013;Peng et al, 2008;Zeng et al, 2010;Zhu and Yoshikawa, 2015). The ways by which a government influences firms' international expansion include appointing executives (Cui and Jiang, 2012), providing valuable information and resources (Lin, 2011), offering various kinds of institutional support (Luo et al, 2010), and building positive connections with host-government entities (Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we posit that the internationalization processes arise from an interaction of the dual objectives (economic and political) of the governments. Fortunately, the phenomena of emerging companies' internationalization are common (Bremmer, 2009;Zeng et al, 2010) and offer a favorable setting for testing our hypotheses. Specifically, we draw on the Chinese construction industry to examine why different SOEs differ in their paces and rhythms of internationalization, as well as in their location choices and product strategies for international expansion; this industry is a government-guided industry containing many involved SOEs with large variations of state capitalism.…”
Section: Introductionmentioning
confidence: 99%